1984
DOI: 10.1148/radiology.153.1.6473802
|View full text |Cite
|
Sign up to set email alerts
|

Renal oncocytoma: new observations.

Abstract: Renal oncocytomas are uncommon, benign tumors that can be treated by local excision or heminephrectomy; their preoperative differentiation from renal cell carcinoma, treated by radical nephrectomy, would be invaluable. A particularly important finding, a central scar--not stressed in previous reports, is frequently demonstrated by CT examination. We evaluated radiographic studies of 18 pathologically confirmed cases of oncocytoma and compared findings with results of CT, sonography, and angiography studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
2
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 0 publications
10
42
2
1
Order By: Relevance
“…Thus, our study correlates with study of Quinn et al [20] (1984) which concluded Oncocytomas can be suggested if a stellate scar is identified within an otherwise homogenous tumor on ultrasound (US) and CT. If the mass appears homogeneous without scar, angiography should be performed.…”
supporting
confidence: 91%
“…Thus, our study correlates with study of Quinn et al [20] (1984) which concluded Oncocytomas can be suggested if a stellate scar is identified within an otherwise homogenous tumor on ultrasound (US) and CT. If the mass appears homogeneous without scar, angiography should be performed.…”
supporting
confidence: 91%
“…In this regard, the diagnostic utility of a number of pre operative investigations has been examined. Despite the identification of radiographic features associated with renal oncocytoma [12], no specific diagnostic appearance has been described [13,14]. Similarly, while the cytological appearance of fine-needle aspirates from these tu mours has occasionally been suggested as a means of pre operative diagnosis [ 15], it is often indistinguishable from that of renal cell cancer [16], Some workers have sought to demonstrate differences between the tumour types on the basis of flow-or image-cytometric analysis of the DNA content of tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Das Onkozytom, welches etwa 7% der malignen Nierentumore ausmacht, oder ein Nierensarkom (1%) kann weder sonographisch noch durch andere bildgebende Diagnostik vom Nierenzellkarzinom sicher differenziert werden. Große Onkozytome (>3 cm) können eine charakteristische zentrale sternförmige Narbe aufweisen [10].…”
Section: Maligne Tumoreunclassified